If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -5 + 2(3x) + 13 = -2 + -2x + (16 + -5) Remove parenthesis around (3x) 2x + -5 + 2 * 3x + 13 = -2 + -2x + (16 + -5) Multiply 2 * 3 2x + -5 + 6x + 13 = -2 + -2x + (16 + -5) Reorder the terms: -5 + 13 + 2x + 6x = -2 + -2x + (16 + -5) Combine like terms: -5 + 13 = 8 8 + 2x + 6x = -2 + -2x + (16 + -5) Combine like terms: 2x + 6x = 8x 8 + 8x = -2 + -2x + (16 + -5) Combine like terms: 16 + -5 = 11 8 + 8x = -2 + -2x + (11) 8 + 8x = -2 + -2x + 11 Reorder the terms: 8 + 8x = -2 + 11 + -2x Combine like terms: -2 + 11 = 9 8 + 8x = 9 + -2x Solving 8 + 8x = 9 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 8 + 8x + 2x = 9 + -2x + 2x Combine like terms: 8x + 2x = 10x 8 + 10x = 9 + -2x + 2x Combine like terms: -2x + 2x = 0 8 + 10x = 9 + 0 8 + 10x = 9 Add '-8' to each side of the equation. 8 + -8 + 10x = 9 + -8 Combine like terms: 8 + -8 = 0 0 + 10x = 9 + -8 10x = 9 + -8 Combine like terms: 9 + -8 = 1 10x = 1 Divide each side by '10'. x = 0.1 Simplifying x = 0.1
| (9b-6)-4(2b+2)=-7 | | 100=34 | | 5-4x=11x | | 5-(6-3n)=2 | | G(x)=x^2+3x-54 | | 12x/4=-2y/2 | | G(x)=x^2+9x+20 | | 2=x/-5 | | 9b-9b=11(b-7)+8(b+12) | | 2y^2+18y+80=0 | | -4/7en-3/7en= | | -8=1x+-12-10 | | (3x-4)(7x+4)=0 | | x^2=36-5x | | 4x-5+2(3x)+17=-2-3x+(9-5) | | 13-x=-1 | | -4/7en--3/7en= | | Y=27x+10.50 | | 4(3y-1)=-40 | | 7x-2(x-4)= | | 10x+5+8=12x-3x+80 | | V+5v=42 | | 6.5k=-240 | | 26+x+3+4=90 | | 4x-3+2(3x)+17=-2-2x+(16-6) | | 2x-80=53+9x | | 81x^3=256x | | -3/5•8/6 | | (1+u)(2u+3)=0 | | f(x)=3x^4-4x^3 | | 60+21.50+21.50=124.50 | | n+124=436 |